Simultaneous saccharification and fermentation of ground corn stover for the production of fuel ethanol using Phanerochaete chrysosporium, Gloeophyllum trabeum, Saccharomyces cerevisiae, and Escherichia coli K011 - Vincent, Micky (The Korean Society for Microbiology and Biotechnology., 2011)
Enzymatic saccharification of corn stover using Phanerochaete chrysosporium and Gloeophyllum trabeum and subsequent fermentation of the saccharification products to ethanol by Saccharomyces cerevisiae and Escherichia coli K011 were achieved. Prior to simultaneous saccharification and fermentation (SSF) for ethanol production, solid-state fermentation was performed for four days on ground corn stover using either P. chrysosporium or G. trabeum to induce in situ cellulase production. During SSF with S. cerevisiae or E. coli, ethanol production was the highest on day 4 for all samples. For corn stover treated with P. chrysosporium, the conversion to ethanol was 2.29 g/100 g corn stover with S. cerevisiae as the fermenting organism, whereas for the sample inoculated with E. coli K011, the ethanol production was 4.14 g/100 g corn stover. Corn stover treated with G. trabeum showed a conversion 1.90 and 4.79 g/100 g corn stover with S. cerevisiae and E. coli K011 as the fermenting organisms, respectively. Other fermentation co-products, such as acetic acid and lactic acid, were also monitored. Acetic acid production ranged between 0.45 and 0.78 g/100 g corn stover, while no lactic acid production was detected throughout the 5 days of SSF. The results of our experiment suggest that it is possible to perform SSF of corn stover using P. chrysosporium, G. trabeum, S. cerevisiae and E. coli K011 for the production of fuel ethanol.